2010
DOI: 10.1016/s1470-2045(10)70106-6
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-receptor blockade and risk of cancer: meta-analysis of randomised controlled trials

Abstract: Summary Background Angiotensin-receptor blockers (ARBs) are a widely used drug class approved for treatment of hypertension, heart failure, diabetic nephropathy, and, recently, for cardiovascular risk reduction. Experimental studies implicate the renin-angiotensin system, particularly angiotensin II type-1 and type-2 receptors, in the regulation of cell proliferation, angiogenesis, and tumour progression. We assessed whether ARBs affect cancer occurrence with a meta-analysis of randomised controlled trials of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
405
4
14

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 430 publications
(431 citation statements)
references
References 37 publications
8
405
4
14
Order By: Relevance
“…Of note, ARBs have been associated with reduced cancer occurrence in patients with essential hypertension and a longer exposure to ARBs has been related with major benefits in cancer patients [119] . Nevertheless, ARBs did not show the ability to reduce considerably cancer development in a meta-analysis of randomized controlled trials [120] .…”
Section: Gpcrs Activated By Hormonesmentioning
confidence: 98%
“…Of note, ARBs have been associated with reduced cancer occurrence in patients with essential hypertension and a longer exposure to ARBs has been related with major benefits in cancer patients [119] . Nevertheless, ARBs did not show the ability to reduce considerably cancer development in a meta-analysis of randomized controlled trials [120] .…”
Section: Gpcrs Activated By Hormonesmentioning
confidence: 98%
“…Also these results need to be taken with caution since beta-blockers and ACEIs were used in the control group of two out of the five trials included in this analysis; hence the results could be from a cancer-protecting effect of these two groups of RAS blockers. 42 A retrospective study analysing 287 patients with advanced non-small-cell lung cancer undergoing first-line platinum-based chemotherapy to examine the use of longterm medication with ACEI and ARB found that patients receiving ACEIs/ARBs had a remarkable estimated survival advantage of 3.1 months (HR 0.56, p = 0.03). 43 Similar data have been observed in other types of cancer.…”
Section: Ras Blockers and Cancermentioning
confidence: 99%
“…They found no significant increase in the risk of cancer in the ARB treatment group (Table 2). Comparison of the analyses by Sipahi and others 2 and by the ATC 3 reveals a striking difference in the raw numeric data for cancer outcomes from 5 trials that were included in both meta-analyses: LIFE, ONTARGET, PROFESS, TRAN-SCEND, and TROPHY. This difference was due to the exclusion from the ATC analysis 3 of patients with known cancer at baseline.…”
Section: Comparison Of 3 Meta-analysesmentioning
confidence: 97%
“…For VALIANT and Val-HeFT, only cancer-related mortality was reported in the final publications, and CHARM did not differentiate between benign and malignant neoplasms when reporting outcomes. [1][2][3] Therefore, none of these trials were included in the primary outcome of the meta-analysis by Sipahi and others. 2 However, for the ATC analysis, 3 the incidence of cancer for all of these trials (VALUE, VALIANT, Val-HeFT, and CHARM) was made available and was included in the pooled analysis.…”
Section: Comparison Of 3 Meta-analysesmentioning
confidence: 99%
See 1 more Smart Citation